Quantification of Percolation from Percolation Tank - Singh, J.; Awasthi, M.K.; Sharma, R.K. (Journal of Soil and Water Conservation, 2022)
Uncertainty in the occurrence of rainfall with respect to time and quantity is a major constraint to agricultural production in rainfed areas. To alleviate the constraint, groundwater is pumped at an unsustainable rate causing continuous water table decline. Groundwater recharge by the rainwater and runoff harvested in percolation tanks can augment the groundwater resource. A study was conducted to quantify percolation from a percolation tank by using water balance approach. The study revealed that the rate of percolation varied from 177.30 to 12.049 m3 per day (48.43 to 2.86 mm/day) during monsoon season when the tank storage varied from 9960 to 5150 m3. In the spring season, the percolation rate varied from 91.78 to 3.067 m3 per day (18.40 to 0.67 mm/day) for tank storage between 3740 and 390 m3. The average rate of percolation over an observation period of 217 days was 39.517 m3 per day. Out of total storage loss of 13620.92 m3 from the tank over an observation period of 217 days, 8615.51 m3 water was lost through percolation and the rest 5005.41 m3 through evaporation. Thus, about 63 per cent of the water loss from percolation tank storage is a gain to the groundwater resource.